Akomodatif Kompilasi Hukum Islam (KHI) Indonesia terhadap Hukum Adat - Sofyan A. P. Kau (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
Compilation of Islamic Law (KHI) Indonesia is the Indonesian fiqh in the language of the law. Called as Fiqh of Indonesia because Indonesia besides tempered personality, also adopted the customary laws that live in the local tradition as part of Islamic law. This paper demonstrates the accommodating attitude KHI with customary law. Among other provisions concerning joint property and inherit each other between the adopted child and the adoptive parents through the institution was borrowed. Both laws were adopted in customary law is the result of ijtihad scholars of Indonesia, because the issues are both not found in Jurisprudence. Indonesian cleric's innovative creations, besides being a form of manifestation of the characteristics of Islamic law that is dynamic and creative, also an Indonesian Islamic identity in the field of law.